Intrarectal artemisinin derivatives. - Nosten, F; van Vugt, M; White, N (1998)
The artemisinin derivatives are the most potent antimalarials. They are rapidly absorbed orally, parenterally and intra-rectally. The latter mode of administration is particularly interesting in rural tropics. Preliminary studies have shown that artemisinin and its derivatives artesunate and artemether are effective when given intrarectally. More studies are needed to establish the optimum regimen.